2008
DOI: 10.2147/tcrm.s6862
|View full text |Cite
|
Sign up to set email alerts
|

Management of laryngopharyngeal reflux with proton pump inhibitors

Abstract: Abstract:There is a lack of consistent guidelines and consensus for the diagnosis of laryngopharyngeal refl ux (LPR). A therapeutic trial with a proton pump inhibitor (PPI) has been suggested to identify patients with LPR. This review focuses on the current diffi culties in diagnosing the disease and examines the evidence for the effectiveness of PPI therapy in suspected refl ux-related laryngeal symptoms. Additionally, mode of action, safety, and tolerability of PPIs are described. A total of 7 placebo-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…However, one study suggested that GORD would only worsen nasal symptom scores but did not cause chronic rhinosinusitis [46]. Studies data are conflicting in role of PPI in LPR as some studies found a higher response when using PPI suggesting complex patterns of LPR, while others did not show additional relief of symptoms compared with placebo [49] although a positive correlation was found between pH Ryan score and total SFAR score in another study which could be related to LPR [17]. RSI score in our study increased in responders with positive AR symptoms, suggesting that having AR increased the symptoms of LPR and vice versa, SFAR score increased with positive LPR symptoms, suggesting that having LPR increased symptoms of AR.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study suggested that GORD would only worsen nasal symptom scores but did not cause chronic rhinosinusitis [46]. Studies data are conflicting in role of PPI in LPR as some studies found a higher response when using PPI suggesting complex patterns of LPR, while others did not show additional relief of symptoms compared with placebo [49] although a positive correlation was found between pH Ryan score and total SFAR score in another study which could be related to LPR [17]. RSI score in our study increased in responders with positive AR symptoms, suggesting that having AR increased the symptoms of LPR and vice versa, SFAR score increased with positive LPR symptoms, suggesting that having LPR increased symptoms of AR.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses show very little difference in pretreatment and posttreatment symptoms compared with placebo, and standard practice shifts to twice daily, then 3 times daily, in cases of refractory LPRD. [24][25][26] A substantial number of patients demonstrate relative resistance to PPIs. 27 Studies on surgical treatment with fundoplication have also been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, high placebo response levels suggested a more complex and multifactorial pathophysiology. 23 Like previous authors, the reviewers concluded that further studies are needed to characterise subgroups of patients with reflux-associated laryngeal symptoms who might benefit from treatment with PPI.…”
Section: Rationalementioning
confidence: 83%
“…This would accord with the magnitude of the placebo effect in TOPPITS. 23 A person's locus of control is either internal (believes to personally control his or her life) or external (believes to be controlled by others, by environmental factors that cannot be influenced or by chance). An external locus of control has been found to be related to higher placebo response.…”
Section: Update On Ph-metry and Manometry In Throat Symptomsmentioning
confidence: 99%